Pengembangan Model Pembelajaran Problem Posing dalam Pembelajaran Matematika - Ramlan M (Paedagogik, 2013)
The objektive of this research is to produce the prototipe of mathematics learning instrument with the characteristics of cooperative laerning of STAD type on the square equation subject that fulfill the criteria of valid, practical, and effective. This research is classified as the developmental research. The model of the instrument development employed in this research referred to the 4-D model wich consisted of defining stage, design stage, development stage, and dissemination stage.